Protection coordination analysis applied at biogas power generation plant - Yulianta Siregar; Wiwanto Tjumar; Naemah Mubarakah; Riswan Dinzi (Institute of Advanced Engineering and Science, 2023)
Biogas from liquid waste from palm oil processing, palm oil mill effluent (POME), can be utilized in biogas power plants as a source of renewable energy (PLTBg). The PLTBg electrical system is equipped with a coordinated protection system. Then, the protection system must also maintain the continuity of electrical service in parts that are not affected by disturbances. Coordination of the protection system is essential. In this research, the electrical transient analysis program (ETAP) carries out the short circuit current analysis, and the coordination of overcurrent protection is constructed from its inverse-definite minimum time characteristics. The analyzed data contributed to selecting the right protection devices. A combination of overcurrent protection, directional protection, and frequency protection change rate supported a reliable electrical power system for a biogas power generation plant as distributed generation. The result shows that modern microprocessor-based protection relays support several protection features in one device and can be integrated into a supervisory control and data acquisition (SCADA)-controlled protection system to enhance their capabilities.